Diaspora and City Diplomacy: A Case Study of the Cooperation Between the Italian-Polish Association of the City and Province of Salerno and Bolesławiec - Raczyński, Rafał; Kowalska, Kamila (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2024)
In recent years, both diasporas and cities have become important non-state actors in international relations. This development has spurred new subcategories of diplomacy, i.e. “diaspora diplomacy” and “city diplomacy.” However, there is a lack of research and publications linking the diplomatic activity of these two actors. The article presents a case study of international cooperation developed between various sub-state actors from Poland and Italy. This collaboration was initiated and jointly implemented by a Polish diaspora organization, with the support of the Polish diplomatic corps. The study aims to show the dynamic interactions and benefits arising from collaboration between different actors operating at the intersection of public, cultural, and economic diplomacy. The article consists of three main sections. In section one, we define the concepts of “diaspora diplomacy” and “city diplomacy.” The second section presents a description of activities undertaken as part of the analyzed project. In the third section, we present the role and importance of the key stakeholders involved in this initiative, highlighting the outcomes and benefits of cross-sector collaboration. W ostatnich latach zarówno diaspory, jak i miasta zyskały miano ważnych niepaństwowych aktorów stosunków międzynarodowych. Jednym z wyrazów takiego stanu rzeczy stało się powstanie nowych subkategorii dyplomacji tj. dyplomacji diaspor oraz dyplomacji miast. Brakuje jednak badań i publikacji, które łączyłyby działania dyplomatyczne tych dwóch aktorów. Artykuł stanowi studium przypadku współpracy międzynarodowej rozwiniętej pomiędzy różnorodnymi podmiotami subpaństwowymi z Polski i Włoch, zainicjowanej i współrealizowanej przez polską organizację diasporyczną, przy wsparciu polskiego korpusu dyplomatycznego. Celem pracy jest ukazanie dynamiki działań i korzyści wynikających ze współdziałania różnych podmiotów w obszarze lokującym się na styku dyplomacji publicznej, kulturalnej i ekonomicznej. Artykuł składa się z trzech zasadniczych sekcji. W części pierwszej definiujemy pojęcia dyplomacji diaspor i dyplomacji miast. Sekcja druga stanowi opis działań podejmowanych w ramach analizowanego przedsięwzięcia. W sekcji trzeciej prezentujemy rolę i znaczenie najważniejszych podmiotów zaangażowanych w realizację inicjatywy. W tej części przedstawiamy również kluczowe efekty i korzyści wynikające z międzysektorowej współpracy.
Dyplomacja diaspor i miast. Studium przypadku współpracy zainicjowanej przez Włosko-Polskie Stowarzyszenie Miasta i Prowincji Salerno oraz Bolesławiec
Keywords: diaspora diplomacy; city diplomacy; diaspora policy; paradiplomacy; Polish migrant organizations; dyplomacja diaspor; dyplomacja miast; polityka diasporyczna; paradyplomacja; organizacje polonijne